CRIMINAL LAW CHALLENGES AND SOLUTIONS IN ARTIFICIAL INTELLIGENCE-BASED CRIME PREVENTION IN INDONESIA - Tri Suyud Nusanto; Aloysius Wisnubroto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The development of artificial intelligence (AI) technology has serious implications for the criminal justice system in Indonesia. The emergence of new forms of crime such as cyber laundering, deepfakes, and digital data manipulation raises questions about who should be held accountable. This study aims to examine the main challenges in applying criminal law to AI-based entities and offer normative and practical solutions to ensure legal certainty. By using a normative juridical approach and a literature review of Indonesian positive legal regulations and doctrines, this study is expected to contribute to the formation of a ius constituendum that is adaptive to the digital era. The results of the study demonstrate the urgency of reforming national criminal law to accommodate the legal status and responsibilities of AI in the Indonesian justice system.